PELESTARIAN UNIT PELAKSANA TEKNIS DINAS (UPTD) MUSEUM SUBAK SEBAGAI DAYA TARIK WISATA BUDAYA DI KABUPATEN TABANAN - Ariningsih, I Gusti Ayu Arya; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2015)
ABSTRACT Unit Pelaksana Teknis Dinas (UPTD) Subak Museum is a museum of agricultural equipment storages, it is located in Tabanan regency. The existence of this museum it is important to remember at this time of our generation are less concerned with the existence of paddy which is the spearhead of human life at the same time has become a culture that is ingrained. It is important to preserve Subak Museum for information and education as well as of course to save a variety of objects related of subak. That assumption is underlying me to choose this topic for research. The topic is "Conservation of Unit Pelaksana Teknis Dinas (UPTD) Subak Museum as Cultural Travel Attractions in Tabanan". The type of data and resources of data used the qualitative data, primary data and secondary data. Collecting data organize by observation, interviews, documentation, and literature study, and research instruments used interview guides. Furthermore the data which was collected will be descriptively by analysis of qualitative data. The analysis of qualitative data it is clearly easy to explain the result and answer the problems that we want to find. Conservation of Subak Museum as Cultural Travel Attractions in this study contains of two definition such as the static and dynamic, but in this research I talk over about the dynamic point. In a dynamic sense such as the creativity how to maintenance, protection but not to change the existing value and reflected through the management, activities and human resources information.
Keywords: Conservation and Museum Subak